Positron Annihilation Spectroscopy of Active Galactic Nuclei - Alexander V. Yushchenko; Yeuncheol Jeong (Journal of Astronomy and Space Sciences, 2019)
A regular and random components in the fluxes of quanta and particles from AGN is investigated. We consider the diffuse component and detect radiative feedback after the passage of cosmic rays and quanta through AGN. The radiation and electron energy distribution functions are dependent on the distribution of matter in AGN. The cross-sections for the single-photon annihilation of positrons in AGN, the fluxes of γ-quanta and the correlation between the energies of positron, γ-quantum and target nucleus with the weight of the nucleus are determined. The two-photon annihilation can be a result of positron’s energy loss. The single-photon annihilation manifests itself in the gas component of AGN and occurs as interaction between positrons and K-shell electrons. It is suitable for identification of the chemical state of investigated media. The comparison with the positron’s detection by PAMELA artificial satellite is made. The production of secondary positrons by cosmic rays and the relationship between the energy of γ-quanta emitted upon the single-photon annihilation and the energy of incident electrons is investigated. The cross sections for positron interactions with bound electrons in AGN allowed obtaining new spectroscopic characteristics of the atoms involved in annihilation.